Propagation of ship waves on a sloping bottom - Do Nascimento, Maria Francisca; Neves, Claudio Freitas; De Freitas MacIel, Geraldo [UNESP] (My University, 2009)
The numerical model FUNWAVE was adapted in order to simulate the generation and propagation of ship waves to shore, including phenomena such as refraction, diffraction, currents and breaking of waves. Results are shown for Froude numbers equal to 0.8, 1.0 and 1.1, in order to verify the refraction of the wave pattern, identify breaking conditions and to investigate the wave generation scheme as a moving pressure at the free surface. © 2009 World Scientific Publishing Co. Pte. Ltd.
Keywords: Breaking conditions; Free surfaces; Ship waves; Sloping bottom; Wave generation; Wave patterns; Coastal engineering; Refraction; Water waves